The Impact of CAMEL ComponenThe Impact of CAMEL Components on Bank Profitability: The Moderating Role of Firm Size in Indonesian Bankingts on Bank Profitability: The Moderating Role of Firm Size in Indonesian Banking - Monica Lyras Ayunda; Edy Suryadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study investigates the determinants of bank profitability in Indonesia using the CAMEL framework with firm size as a moderating variable, grounded in signaling theory. The research examines how capital adequacy, asset quality, earnings capacity, operational efficiency, and liquidity function as financial signals that influence bank profitability. The sample consists of banking companies listed on the Indonesia Stock Exchange during the period 2020-2024, comprising 140 firm-year observations. Multiple linear regression and Moderated Regression Analysis (MRA) are employed to assess both direct and moderating effects on profitability, measured by Return on Assets (ROA). The empirical results indicate that Net Interest Margin (NIM) has a positive and statistically significant effect on ROA, while the Operating Expenses to Operating Income Ratio (BOPO) and Loan to Deposit Ratio (LDR) exhibit significant negative effects, underscoring the importance of earnings efficiency, cost control, and prudent liquidity management in enhancing bank profitability. In contrast, Capital Adequacy Ratio (CAR) and Non-Performing Loans (NPL) do not show significant direct effects on ROA, suggesting that regulatory standardization and effective risk management may limit their short-term influence on profitability. Furthermore, firm size does not directly affect ROA but significantly moderates the relationship between credit risk and profitability, indicating that larger banks are better equipped to absorb adverse credit risk. This study contributes to the banking literature by providing empirical evidence from an emerging market context and reinforcing the relevance of signaling theory in explaining how financial indicators shape bank profitability.